Holocene Sedimentary Record from the Sunda Shelf off Peninsular Malaysia: Insights from Elemental, Isotopic and Bulk Sediment Magnetic Susceptibility Analyses - Hindes, Haley; NC DOCKS at East Carolina University (2023)
Post-Last Glacial Maximum (since ca. 20,000 cal yr BP) sediments of the Sunda Shelf (southern South China Sea) are generally thin, with the exception of incised valleys where thicker accumulations tend to occur. These valleys provide a sedimentary record that preserves Holocene environmental changes. In the summer of 2014, two ca. 2 m gravity cores were collected on the Sunda Shelf in ca. 60 m of water ca. 52 km from the mouth of the Terengganu River off northeast peninsular Malaysia. Both cores were sampled in 1 cm contiguous intervals and analyzed for magnetic susceptibility of bulk sediment (BMS), elemental composition (X-ray fluorescence, XRF), and oxygen and carbon stable isotopes on the planktonic foraminifer Globigerinoides ruber. The chronology of the cores, based upon eight AMS radiocarbon age estimates on the benthic foraminifer Cavarotalia annectens, covers most of the Holocene. According to previous work, the Holocene evolution of the Sunda Shelf was largely controlled by the transgression of the South China Sea (SCS) shoreline following the Last Glacial Maximum. Several sea-level curves suggest sea level in the area had reached ca. -60 m by the start of the Holocene (ca. 11,700 cal yr BP). According to this study, at ca. 10,000 cal yr BP, the Sunda Shelf off northeast Peninsular Malaysia was already covered by ca. 30 m of water, evident by the presence of benthic foraminifera and marine mud throughout both cores. The study area transitioned from a shallow, muddy, nearshore environment to an open shelf environment (ca. 60 m water depth and at least 50 km from shore) during the 10,000 - 6,400 cal yr BP time interval. This is indicated by steadily decreasing Al, Ti, and Fe concentrations up-core, steadily increasing Ca concentrations up-core, and the first occurrence of planktonic foraminifera at ca. 7,000 cal yr BP. Between 6,000 - 4,000 cal yr BP, previous studies indicate the mid-Holocene sea-level highstand was reached. This study suggests the presence of a possible diastem at ca. 6,400 cal yr BP ...